The Influence of Brand Image, Electronic Word of Mouth (E-WoM) and Influencer Endorsement on Interest in Buying Zalora Indonesia E-Commerce in Yogyakarta City - Wiyoga, Adhe; Sugandini, Dyah; Laksana, Dwi Hari (Journal of International Conference Proceedings, 2023)
This study aims to determine the effect of brand image, electronic word of mouth and influencer endorsement on purchase intention. The method used in this study is a quantitative method, the data used were obtained from questionnaires collected from 100 respondents. The sampling technique in this study uses purposive sampling. The analysis technique in this research is statistical and quantitative analysis (multiple linear regression). The results of this study indicate that simultaneously and partially the variables of brand image, electronic word of mouth and influencer endorsement have a positive and significant effect on purchase intention in Zalora Indonesia's e-commerce in Yogyakarta City. Therefore, it is important for Zalora Indonesia to maintain its brand image, maintain good responses from its customers through the products and services provided, and choose good endorsement influencers in order to encourage consumer buying interest in products sold through Zalora Indonesia.